Bioinformatic analysis of genetic factors from human blood samples and postmortem brains in Parkinson’s disease - Yao, Longping; Lin, Kai; Zheng, Zijian; Koc, Sumeyye; Zhang, Shizhong; Lu, Guohui; Skutella, Thomas (Oxidative medicine and cellular longevity, 2022)
Parkinson’s disease (PD) is one of the most prevalent neurodegenerative disorders characterized by motor and nonmotor symptoms due to the selective loss of midbrain dopaminergic neurons. Pharmacological and surgical interventions have not been possible to cure PD; however, the cause of neurodegeneration remains unclear. Here, we performed and tested a multitiered bioinformatic analysis using the GEO and Proteinexchange database to investigate the gene expression involved in the pathogenesis of PD. Then we further validated individual differences in gene expression in whole blood samples that we collected in the clinic. We also made an interaction analysis and prediction for these genetic factors.
Gesehen am 09.02.2023